Road to employee commitment: the role of empowerment, leadership and culture. (2018) - Thomas, Resmi Ann; Pentareddy, Sandhya; Suganthi, L.; Joy, Gemini V.; Anbuudayasankar, S.P.
This exploratory research seeks to identify the relationships between the leadership, empowerment and commitment within the integrated model of competing values framework (CVF) of organisational culture. A conceptual model which relates the constructs to commitment is developed. The study attempts to use a social constructionist approach and scenario planning, which falls under the broader realm of qualitative analysis. Hypothetical cases are used to develop two scenarios. The study proposes an integrated model of CVF, and also provides greater understanding of the competencies required in the organisation to move from one competing value quadrant to another. The paper helps managers gain better understanding of managerial roles, their inter-relationships to each other and how to apply them more effectively. It further develops an understanding by providing a model of how to transform an organisation to be a self-sustained one. The study also brings forth a constructive approach in management.